2016
DOI: 10.1007/s40620-016-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of chronic renal replacement therapy in patients with cancer: data from kidney and cancer registries in Basse-Normandie

Abstract: Aims To estimate the incidence of chronic dialysis in patients with a history of cancer and assess how renal replacement therapy is initiated in this population. Methods We merged data from cancer registries and hospital databases in one French region to identify patients with an incident cancer between 2001 and 2008 who started chronic dialysis. Results Mean participation time was 3.4 ± 2.7 years. Males comprised 58.5 % of participants. During the study period, 74 chronic dialysis treatments were initiated. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Eligible studies included incident chronic dialysis patients (n = 42) 2-4,6,8,9,13-48 and patients with CKD known to nephrology (n = 6). 5,49-53 Study designs included retrospective cohort studies (n = 27), 2,3,5,6,14-16,19-24,26,28,31-36,38,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eligible studies included incident chronic dialysis patients (n = 42) 2-4,6,8,9,13-48 and patients with CKD known to nephrology (n = 6). 5,49-53 Study designs included retrospective cohort studies (n = 27), 2,3,5,6,14-16,19-24,26,28,31-36,38,47…”
Section: Resultsmentioning
confidence: 99%
“…13 No randomized control trials were found in the search. The majority of studies were conducted in Europe (n = 26; 22 unique cohorts) 2,8,9,15-19,22-25,29,30,33,36,40-43,45-48,50,51 ; 11 studies were conducted in North America 3-6,14,21,26,28,31,52,53 (Canada, n = 9; 8 unique cohorts). Study cohort sizes ranged from 43 to 45 785 persons.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that cancer is an obstacle to access to self‐care therapy . We recently showed that the incidence of chronic renal replacement therapy in cancer patients is not higher compared to the incidence of dialysis in the general population despite their higher risk of chronic renal disease . However to our knowledge, there is no study focusing on access to pre‐dialysis programs and to chronic dialysis in cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that the RRT group revealed a significantly higher 7-year cancer incidence rate than did the general population and risk for blood, liver, colorectal, oral, breast, renal, upper urinary tract, and bladder cancer development was significantly higher than in the general population. In Europe, Bechade et al [ 98 ] used the data from cancer registries and hospital databases in one French region and searched for subjects with an incident malignancy between 2001 and 2008 who started RRT. They found that the incidence rate of RRT in the population of incident malignancy was 370 per million population/year (74 events/199,809 person-years).…”
Section: Introductionmentioning
confidence: 99%
“…Age-adjustment standardized incidence ratio was 1.26, (95 % CI 0.98-1.57, p = 0.55). In contrast to the American [ 95 ] and Taiwan [ 97 ] counterparts, they suggested that the standardized incidence ratio of chronic dialysis initiation was not significantly differed between patients with malignancy and the general population [ 98 ]. There are several explanations for increased cancer incidence in the dialysis population such as ESRD-associated immunodeficiency and nutritional abnormalities [ 99 109 ].…”
Section: Introductionmentioning
confidence: 99%